PENGARUH SERVANT LEADERSHIP DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA PALU (KPP PRATAMA PALU) - AJIS, SIGITTRIADI (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2017)
The objective of this research is to determine the influence of servant leadership and work motivation on the performance of employees at the Pratama Tax Office Palu. Independent variables include servant leadership (X1) and work motivation (X2); dependent variable is employees? performance (Y). The research is quantitative descriptive and uses quantitative data from primary and secondary sources. Population in this study involves 104 employees with 51 samples selected by proportional random sampling. Data analysis uses multiple linear regression analysis method. The results of this study indicate that servant leadership and work motivation simultaneously and partially influence the performance of employees.